Crystal structure of 1′, 1′′-dimethyl-4′-(4-cholorophenyl)dispiro[11H-indeno[1, 2-b]quinoxaline-11, 2′-pyrrolidine-3′, 3′′-piperidin]-4′′-one. (February 2015) - Nagalakshmi, R.A.; Suresh, J.; Malathi, K.; Kumar, R. Ranjith; Lakshman, P. L. Nilantha
No abstract available